The relevance of the pretreatment on the chemical modification of cellulosic fibers - Aguado, Roberto (2019)
Cationized fibers and other kinds of chemically modified fibers impart many advantages in papermaking, but unfeasibly long reaction times are necessary to attain acceptable degrees of substitution, due to the low reactivity of bleached kraft pulps. In this work, different aqueous pretreatments were tested in order to activate cellulose towards a 60 min-long etherification with a quaternary ammonium reagent. Severe decrystallization treatments, namely alkalization with NaOH 20%, NaOH/urea or FeTNa, conducted to the best reactivity results (substitution from 2 to 10%), but the fiber properties were harshly affected. Pretreatments involving H3PO4 at different concentrations were also performed, with distinct results, from unnoticeable effects at 20% to amorphization and excessive depolymerization at 80%. Finally, aqueous ammonium thiocyanate was tested as activator and had little effect on fibers, although the addition of ammonia resulted in high degrees of substitution, while maintaining the pulps’ capability to retain inter-fiber water and cellulose I as the prevalent allomorph.